INTER-BUDGET EQUALIZATION IN FORMING THE INCOME POTENTIAL OF THE REGION (American Journal of Interdisciplinary Research and Development, 2022)
One of the features of the organization of local budgets of the Republic of Uzbekistan is the centralization of revenue sources and expenditure powers at the level of the state budget, the formation of local budgets "from top to bottom", as a result of which their often observed loss-making. This leads to the fact that, subject to the rational use of gratuitous deductions from the higher budget, the subordinates in most of the administrative-territorial entities of Uzbekistan observe medium or low financial independence of the territories from the center.